gente mim ajuda nessa questão !
Anexos:
![](https://pt-static.z-dn.net/files/d3a/70636f1398be1ac6fd80832d6314a18f.jpg)
Soluções para a tarefa
Respondido por
1
Calcula o determinante:
![cos^2x*(cos^2x+sen^2x)-sen^2x(cos^2x+sen^2x)=1\\\\
cos^4x+cos^2x*sen^2x-sen^2x*cos^2x-sen^4x=1\\\\
cos^4x-sen^4x=1\\\\
cos^2x*(cos^2x+sen^2x)-sen^2x(cos^2x+sen^2x)=1\\\\
cos^4x+cos^2x*sen^2x-sen^2x*cos^2x-sen^4x=1\\\\
cos^4x-sen^4x=1\\\\](https://tex.z-dn.net/?f=cos%5E2x%2A%28cos%5E2x%2Bsen%5E2x%29-sen%5E2x%28cos%5E2x%2Bsen%5E2x%29%3D1%5C%5C%5C%5C%0Acos%5E4x%2Bcos%5E2x%2Asen%5E2x-sen%5E2x%2Acos%5E2x-sen%5E4x%3D1%5C%5C%5C%5C%0Acos%5E4x-sen%5E4x%3D1%5C%5C%5C%5C%0A%0A%0A)
Se x for 0, cos 0 = 1 e sen 0 = 0, então 1 + 0 = 1 e satisfaz a equação.
a)0.
Se x for 0, cos 0 = 1 e sen 0 = 0, então 1 + 0 = 1 e satisfaz a equação.
a)0.
Perguntas interessantes